Effect of the external pressure on the plastic instability of thin-walled tubes - Guven, U. (SAGE PUBLICATIONS LTD, 2009)
In the present work the effects of an external pressure on the plastic instability and the limit strains of thin-walled tubes are investigated using Swift's criterion. The analysis is based on a plane stress state and the assumptions normally used in this type of study are applied. The effects of three different necking criteria are investigated in the absence of an axial load. The presented results indicate that the application of an external pressure can be advantageous in certain circumstances. It is also shown that the bursting pressure increases with an increase in the external pressure.
Keywords: thin-walled tubes; plastic instability; external pressure; bursting pressure; Engineering